EXPLORATORY STUDY ON FACTORS AFFECTING THE CREDIBILITY OF SOCIAL INFLUENCERS ON FACEBOOK - Dr.Deepa Ittimani Tholath, Khadeeja Bilquees (International Journal of Advanced Science and Technology, 2020)
Companies have started depending heavily on Social Influencers in India. This paper seeks to understand the credibility of Facebook social influencers among students in the age group of 18 to 25. Focus group study was carried out with a group of 25 students who had regularly followed social influencers for opinions on Facebook. The results elucidate the positive and negative factors that affect the credibility of the Social Influencers on Facebook.